Teacher Performances in Implementation of Learning at State Elementary School in Kecamatan Gunung Toar Kabupaten Kuantan Singingi - Jas, Jaspar; Alvi, Ria Rizkia (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this study was to determine level of teacher performance in implementing learning activities at State Elementary School are, in planning learning activities, carry out learning activities, evaluate and follow-up of learning activities. This is a descriptive study with a quantitative approach. The population is 150 people. The samples in this study using simple random sampling, the samples are 108teachersat State Elementary School in Gunung Toar Kabupaten Kuantan Singingi. The instrument used was a questionnaire containing 40 items statement. The performance of teachers in learning activities at State Elementary School in Gunung Toar kabupaten Kuantan Singingi to be assessed and measured by indicators of learning to plan, implement and evaluate learning and follow-up of learning activities. The results show that the performance of teachers in learning activities at State Elementary School in GunungToar Kabupaten Kuantan Singingi in medium category. Thus, the performance of teachers in the implementation of learning in the state Elementary School in planning, implementing and evaluating the learning is moderate which means it needs to be improved again.